Solubility Data of the Bioactive Compound Piperine in (Transcutol + Water) Mixtures: Computational Modeling, Hansen Solubility Parameters and Mixing Thermodynamic Parameters - Faiyaz Shakeel; Nazrul Haq; Sultan Alshehri (Molecules, 2020)
The solubility values and thermodynamic parameters of a natural phytomedicine/nutrient piperine (PPN) in Transcutol-HP (THP) + water combinations were determined. The mole fraction solubilities (xe) of PPN in THP + water combinations were recorded at T = 298.2–318.2 K and p = 0.1 MPa by the shake flask method. Hansen solubility parameters (HSPs) of PPN, pure THP, pure water and THP + water mixtures free of PPN were also computed. The xe values of PPN were correlated well with “Apelblat, Van’t Hoff, Yalkowsky–Roseman, Jouyban–Acree and Jouyban–Acree–Van’t Hoff” models with root mean square deviations of < 2.0%. The maximum and minimum xe value of PPN was found in pure THP (9.10 × 10−2 at T = 318.2 K) and pure water (1.03 × 10−5 at T = 298.2 K), respectively. In addition, HSP of PPN was observed more closed with that of pure THP. The thermodynamic parameters of PPN were obtained using the activity coefficient model. The results showed an endothermic dissolution of PPN at m = 0.6–1.0 in comparison to other THP + water combinations studied. In addition, PPN dissolution was recorded as entropy-driven at m = 0.8–1.0 compared with other THP + water mixtures evaluated.